To study the level of nitric oxide in exhaled air in pregnant women with bronchial asthma as a monitoring of disease control and prediction of asthma-associated obstetric complications: Observational comparative study - Alexander A. Pashchenko; Yulia E. Dobrokhotova; Daria S. Fomina (IP Berlin A.V., 2024)
Aim. To determine the clinical significance of the level of nitric oxide in exhaled air (NOex) for optimizing the control of bronchial asthma (BA) in pregnant women in order to reduce asthma-associated obstetric complications. Materials and methods. A cohort comparative study was conducted with the participation of 80 pregnant women in the third trimester of pregnancy against the background of asthma with varying degrees of severity and level of control, with an assessment of the frequency of asthma-associated obstetric complications. The main group consisted of 40 patients with a prospective determination of the level of BA control and inflammatory activity against the background of inhaled glucocorticosteroid + long-acting b2-agonist using a study of nitric oxide levels in exhaled air. The comparison group included 40 patients undergoing therapy with inhaled glucocorticosteroids + long-acting b2-agonist or monotherapy with inhaled glucocorticosteroids with standard methods of outpatient monitoring of pregnancy against the background of asthma (without determining the level of NOex). The instrumental examination was presented by the determination of a surrogate noninvasive marker of inflammation - nitric oxide in exhaled air was determined using a portable NOex detection device (NIOX MONO; Aerocrine AB, Sweden). Results. The study of nitric oxide in exhaled air demonstrated the presence of poorly controlled inflammation of the mucous membrane of the respiratory tract in 22.5% of patients at the beginning of the third trimester, the average NOex values were - 18.75±2.86 ppb. A strong correlation was determined between the values of nitric oxide levels in exhaled air and systolic blood pressure in the third trimester in patients from the main group (Rs=0.84; Rs 0.05=0.31). Decrease in NOex averages (14.87±1.65 ppb) in pregnant women, it occurred as a result of changes in the volume of pharmacotherapy with inhaled glucocorticosteroids and measures to control the strict adherence of patients to anti-asthmatic therapy. Achieving complete control of asthma as a result of screening determination of nitric oxide in exhaled air and selection of optimal anti-asthmatic therapy was accompanied by a 2-fold decrease in the frequency of asthma-associated hypertensive disorders and surgical deliveries in pregnant women from the main group. Conclusion. Modern approaches to the monitoring and therapy of pregnant women with asthma should be based on the study of subclinical inflammation of the mucous membrane of the respiratory tract. The screening method for determining the level of a biomarker of inflammation of the bronchial tree epithelial mucosa - nitric oxide in exhaled air allows to determine the level of BA control, meets the requirements of maximum safety and minimally invasive for use in pregnant women.